Utility of continuous glucose monitoring for identifying silent hypoglycemia in fructose-1,6-bisphosphatase deficiency: a pilot prospective evaluation - Goksoy, Emine; Kumru Akin, Burcu (Frontiers in Endocrinology, 2025)
Background and objectiveFructose-1,6-bisphosphatase (FBPase) deficiency is a rare gluconeogenic disorder characterized by hypoglycemia, lactic acidosis, hyperuricemia, and ketosis, triggered by fasting or infection. Although dietary management aims to prevent hypoglycemia, accurate tools to monitor asymptomatic episodes are lacking. Continuous glucose monitoring (CGM) has not been systematically evaluated in FBPase deficiency. This study aimed to assess the utility of CGM in detecting silent hypoglycemia and its relationship with dietary management.MethodsTen genetically confirmed patients underwent blinded CGM using the Medtronic iPro2™ system. CGM metrics included time below range (TBR <70 mg/dL [<3.9 mmol/L]), time in range (TIR 70–150 mg/dL [3.9–8.3 mmol/L]), and time above range (TAR >150 mg/dL [>8.3 mmol/L]). Correlations with biochemical, clinical, and nutritional variables were analyzed using Pearson or Spearman tests, and categorical comparisons were conducted with Fisher’s exact test. Multiple testing was controlled using the Benjamini–Hochberg procedure (significance at FDR-adjusted p<0.05).ResultsDespite using uncooked/modified cornstarch (UCCS/MCS) and frequent feeding (all but one patient), asymptomatic hypoglycemia occurred in some patients. Mean TBR was 11.2 ± 31.2% (Median: 1, Range:0-100). Higher UCCS/MCS dosing correlated with fewer annual metabolic attacks (ρ=−0.854, p-adj=0.002), higher TIR (ρ=0.899, p-adj=0.002), and lower TBR (ρ=−0.917, p-adj=0.003). Patients with TBR≥2% had more annual crises (p=0.003), lower UCCS/MCS dosing frequency (p=0.019), and more hepatic steatosis (p=0.048). Ketonuria correlated with attack frequency (r=0.846, p-adj=0.026). Hepatosteatosis was associated with greater annual attacks (p-adj=0.028).ConclusionThis, to the best of our knowledge, is the first systematic pilot study of CGM in FBPase deficiency, suggesting a potential role in detecting silent hypoglycemia and informing individualized dietary strategies.